Cross-Cultural Analysis of Social Capital of Russian Society - A N Tatarko (Peoples' Friendship University of Russia (RUDN University), 2012)
A psycho-semantic research of the social capital of the institutions of the Russian society has been carried out. The cross-cultural distinctions in the perceived social capital of the institutions are analyzed.